2008
DOI: 10.1093/bjsw/bcm044
|View full text |Cite
|
Sign up to set email alerts
|

The Authentic Warmth Dimension of Professional Childcare

Abstract: The emotional, social and academic problems of children and young people in public care have long been documented and many researchers have named the chief culprits as a deeply flawed corporate care system and an unsympathetic education establishment. While the need for major improvements to both corporate care and education is recognized, in this paper, a perspective, which links early childhood experiences with restricted life outcomes, is presented and it is argued that it is parental rejection (often accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Feeling connected to an educational setting has been found to be associated with school success (McLaughlin and Clarke 2010; Resnick et al 1997). The identification of support from family members is consistent with findings that improving the parenting experiences and emotional support provided to vulnerable young people can lead to improved social and academic outcomes (Cameron and Maginn 2008;C4EO 2009;Gallagher et al 2004).…”
Section: Discussionsupporting
confidence: 54%
“…Feeling connected to an educational setting has been found to be associated with school success (McLaughlin and Clarke 2010; Resnick et al 1997). The identification of support from family members is consistent with findings that improving the parenting experiences and emotional support provided to vulnerable young people can lead to improved social and academic outcomes (Cameron and Maginn 2008;C4EO 2009;Gallagher et al 2004).…”
Section: Discussionsupporting
confidence: 54%
“…• personal characteristics: open-minded and accepting of child's background, tolerant, flexible, easy going, organised, consistent (enforcement of rules), deep love or concern for children, realistic, warm, child oriented, respectful, show love and affection, stable, caring, loving, fair, persistent, committed, trustworthy, able to provide reasonable discipline and set limits (Buehler, Cox, & Cuddeback, 2003;Cameron & Maginn, 2008;Crum, 2010;Sinclair & Wilson, 2003a;Whiting & Lee, 2003);…”
Section: Characteristics Of Good Foster Carersmentioning
confidence: 99%
“…Jackson, Ajayi, and Quigley (2005) found that among university students who had been in care, the single most important factor was having a significant adult, usually a foster carer, who took an interest and sustained the young person's educational commitment and ambitions. The challenge for the care system, argued Cameron and Maginn (2008), is to provide the quality of care and support that is to be found not just in the average family home, but in the families that provide optimal stimulation and support for social and educational development. In the USA, Proctor et al (2010) found that among young children who had been fostered, about two-thirds made stable, long-term positive adjustments to their new family situation; such adjustment was assisted where there had been a lower level of abuse and placements were stable.…”
Section: Education Social Class and Children In Carementioning
confidence: 99%